PEMBUATAN PURWARUPA SISTEM INFORMASI PERSEDIAAN OPTIK STUDI KASUS: UD AGNES, MALANG - Prasetyo, Waluyo (Universitas Nahdlatul Ulama Sidoarjo, 2016)
UD Agnes/Agnes Optic (AO) was established in 1990 and located at Jalan Imam Bonjol Kota Batu in Malang. This business is engaged in optical products and services. In this study, the research focus is product of eyeglass lenses. OA business development process has faced obstacles in inventory problem and manual restock process. During this time inventory management has not been managed well so it takes a long time to check inventory stock. EOQ method is used to calculate the inventory in gaining restock time and reduce stock inventory searching time so as to produce information about costs and benefits in each period. The result obtained are optimal restock time period for each stock, reduction of searching time inventory, and information cost and the benefits obtained by AO.